Host Delivered RNAi of Two Cuticle Collagen Genes, Mi-col-1 and Lemmi-5 Hampers Structure and Fecundity in Meloidogyne incognita - Banerjee, Sagar; Gill, Sarvajeet S.; Gawade, Bharat H.; Jain, Pradeep K.; Subramaniam, Kuppuswamy; Sirohi, Anil (Frontiers in Plant Science, 2018)
Root-knot nematodes have emerged as devastating parasites causing substantial losses to agricultural economy worldwide. Tomato is the most favored host for major species of root-knot nematodes. Control strategies like use of nematicides have proved to be harmful to the environment. Other control methods like development of resistant cultivars and crop rotation have serious limitations. This study deals with the application of host generated RNA interference towards development of resistance against root-knot nematode Meloidogyne incognita in tomato. Two cuticle collagen genes viz. Mi-col-1 and Lemmi-5 involved in the synthesis and maintenance of the cuticle in M. incognita were targeted through host generated RNA interference. Expression of both Mi-col-1 and Lemmi-5 was found to be higher in adult females followed by egg masses and J2s. Tomato var. Pusa Ruby was transformed with the RNAi constructs of these genes to develop transgenic lines expressing the target dsRNAs. 30.80-35.00% reduction in the number of adult females, 50.06-65.73% reduction in the number of egg mass per plant and 76.47-82.59% reduction in the number of eggs per egg mass were observed for the T1 events expressing Mi-col-1 dsRNA. Similarly, 34.14-38.54% reduction in the number of adult females, 62.34-66.71% reduction in number of egg mass per plant and 67.13-79.76% reduction in the number of eggs per egg mass were observed for the T1 generation expressing Lemmi-5 dsRNA. The multiplication factor of M. incognita reduced significantly in both the cases and the structure of adult females isolated from transgenic plants were heavily distorted. This study demonstrates the role of the cuticle collagen genes Mi-col-1 and Lemmi-5 in the structure and development of M. incognita cuticle inside the host and reinforces the potential of host generated RNA interference for management of plant parasitic nematodes.